Concomitant genetic alterations having greater impact on the clinical benefit of EGFR‐TKIs in EGFR‐mutant advanced NSCLC than BIM deletion polymorphism. Issue 1 (19th May 2020) - Liu, Si‐Yang; Zhou, Jia‐Ying; Li, Wen‐Feng; Sun, Hao; Zhang, Yi‐Chen; Yan, Hong‐Hong; Chen, Zhi‐Hong; Chen, Chun‐Xiang; Ye, Jun‐Yi; Yang, Jin‐Ji; Zhou, Qing; Zhang, Xu‐Chao; et al.
Abstract: Background: In previous studies, the predictive role of BIM deletion polymorphism with respect to responses to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) has been controversial. The potential reasons for these inconsistent findings were unknown. Methods: Data from CTONG0901 clinical trial and medical records of Guangdong Lung Cancer Institute (GLCI) were retrospectively pooled. A total of 194 and 141 EGFR ‐mutant non‐small cell lung cancer (NSCLC) patients treated with first‐ and second‐generation EGFR‐TKIs were examined in the CTONG0901 and GLCI cohorts, respectively. Sixty‐eight patients were treated with third‐generation EGFR‐TKIs in the GLCI cohort. The BIM gene status was examined by next‐generation sequencing. Results: The frequency of BIM deletion polymorphism was 11.3% and 17.0% in CTONG0901 and GLCI cohorts, respectively. For first‐ and second‐generation EGFR‐TKIs in CTONG0901 cohort, objective response (ORR) was 54.5% in BIM deletion group versus 56.4% in wild‐type BIM group ( P = .87); disease control rate (DCR) was 90.9% versus 88.4% ( P = 1.00); progression‐free survival (PFS) was 10.5 versus 11.2 months ( P = .59); and overall survival (OS) was 20.5 versus 20.5 months ( P = .73). In GLCI cohort, ORR was 54.2% versus 60.7% ( P = .55); DCR was 91.7% versus 96.6% ( P = .27); PFS was 10.1 versus 11.6 months ( P = .63); and OS was 58.5 versus 45.0 months ( P = .93). For third‐generation EGFR‐TKIs, ORR was 18.2% versus 63.2% ( P = .02); DCR was 81.8% versus 96.5%, ( P = .12); PFS was 5.8 versus 9.0 months ( P = .13); and OS was 30.0 versus 24.8 months ( P = .85). Cox regression analysis showed that concomitant genetic alterations could adversely affect the response to EGFR‐TKIs, but not BIM deletion. Conclusions: The presence of BIM deletion showed no relation to an impaired response to first‐, second‐, and third‐generation EGFR‐TKIs in NSCLC patients. The factors influencing the response of EGFR‐TKIs were concomitant genetic alterations, but not BIM deletion.